2011
DOI: 10.4049/jimmunol.1000808
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Targeted NY-ESO-1 to Mannose Receptor or DEC-205 In Vitro Elicits Dual Human CD8+ and CD4+ T Cell Responses with Broad Antigen Specificity

Abstract: Immunization of cancer patients with vaccines containing full-length tumor Ags aims to elicit specific Abs and both CD4+ and CD8+ T cells. Vaccination with protein Ags, however, often elicits only CD4+ T cell responses without inducing Ag-specific CD8+ T cells, as exogenous protein is primarily presented to CD4+ T cells. Recent data revealed that Ab-mediated targeting of protein Ags to cell surface receptors on dendritic cells could enhance the induction of both CD4+ and CD8+ T cells. We investigated in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 40 publications
1
99
1
Order By: Relevance
“…DEC-205 is currently the only receptor which has been visualized on most DC in the T cell area of secondary lymphoid tissues, which are the sites for the generation of immunity and tolerance in mouse models and humans (7,21). Targeting of DEC-205-expressing DC by either chimeric antigen-antibody complexes or recombinant vectors has been proposed to be an effective approach to improve immune responses (7,57). DC draining the skin were found to be FSC high DEC-205 ϩ CD11c ϩ CD8 Ϫ cells.…”
Section: Discussionmentioning
confidence: 99%
“…DEC-205 is currently the only receptor which has been visualized on most DC in the T cell area of secondary lymphoid tissues, which are the sites for the generation of immunity and tolerance in mouse models and humans (7,21). Targeting of DEC-205-expressing DC by either chimeric antigen-antibody complexes or recombinant vectors has been proposed to be an effective approach to improve immune responses (7,57). DC draining the skin were found to be FSC high DEC-205 ϩ CD11c ϩ CD8 Ϫ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-presenting cells that were treated with NY-ESO-1 targeted to the CLRs DEC-205 and MR presented a peptide repertoire that was distinct from cells treated with soluble protein. 36 Consequently, targeting antigens to DC-SIGN via both neck and CRD domains may provide a means to broaden the peptide repertoire that is presented to T cells.Apart from mediating pathogen binding and internalization, DC-SIGN is known to activate intracellular signal pathways on pathogen recognition. The receptor is associated with a signalosome complex consisting of the scaffold proteins LSP1, KSR1, and CNK and the kinase Raf-1.…”
mentioning
confidence: 99%
“…17 Other authors have demonstrated that inhibition of endosomal acidification either improved or had no effect on the cross-presentation. [47][48][49] These discrepancies indicate that endosomal acidification plays a critical role for some epitopes, but might be detrimental for others, which may relate to destruction of some epitopes by proteases active in the different test situations.…”
Section: Discussionmentioning
confidence: 95%